ANALISIS SOSIAL TERHADAP KEBERADAAN "ANAK-ANAK AIBON" DI DISTRIK MERAUKE - Trinovianto George Reinhard Hallatu; Hubertus Oja (SOCIETAS, 2016)
This study aims to identify and analyze the social existence of  “aibon children” in the District of Merauke, Merauke Regency. The type of this research is the study obervasional with descriptive analysis techniques. Data were collected through interviews and observations. The results showed that the majority of aibon children in Merauke District comes from children under the age attending primary school and also children who drop out of school. The main causes them to become aibon children is family economic factors plus environmental influences. Analysis of the social side shows that children aibon this time it had never been observed until they become aibon children who are preoccupied with their lives-paced as it is while looking for good money by begging, waiting and keeping parking, help with the dishes, etc. Handling aibon children expected to not only be the responsibility of the government through social services, but it takes the role of all parties such as the police, NGOs and communities.